The determinants of virtual learning environment (VLE) system adoption attitude among teachers in national secondary schools in Kuala Lumpur - Shashi Kumar Nair, Arumagam (2016)
Virtual Learning Environment System (VLE) is one the current trending technology in education globally. The Virtual Learning Environment (VLE) system has enable to bridge teacher-student-parent communication through its various advantageous functionalities. In Malaysia, the Ministry of Education has joined the global leap of adapting the Virtual Learning Environment (VLE) technology via the introduction of Frog Virtual Learning Environment (VLE) system in 2012. This initiative under the project, 1BestariNet was coupled with high speed broadband access that bridges the digital divide of all schools in the Nation. However, the utilization of the Frog Virtual Learning Environment (VLE) system has seen a low uptake by its stakeholders. Hence, this study aims to investigate the determinants of Virtual Learning Environment (VLE) system adoption attitude among teachers, specifically secondary school teachers in Kuala Lumpur. This study administered the survey methodology for data collection from 89 secondary schools located in three zones in Kuala Lumpur namely zone Bangsar/Pudu, zone Sentul and zone whereby 366 secondary school teachers were chosen as the sample for this study. A disproportionate stratified sampling procedure was used to select respondents from the respective schools within the zone. Five hypotheses were proposed in regards to the determinants of Frog Virtual Learning Environment (VLE) system adoption attitude. A structured questionnaires consisting 35 questions were adopted from previous scholars for this study in order to measure five variables namely Frog Virtual Learning Environment (VLE) System adoption attitude, perceived usefulness, and perceived ease of use, organizational culture and self-efficacy. As of from the 800 questionnaires handed out, only 336 were usable after the outlier assessment thus yielding a response rate of 42.0%. The research was analyzed using descriptive as well as inferential statistics in order to measure the relationship of the variables and draw the inferences between the independent variables and the dependent variable. The research result indicated that there are relationships which exist between the determinants and Frog Virtual Learning Environment (VLE) System adoption attitude. In concluding the research, the academic and managerial implications as well as suggestion for future research was discussed